Fabrication of Buccal Dissolving Tetrahydro Curcumin Loaded Polyvidone Fiber Mat: Synthesis, Characterization, and In Vitro Evaluations - Ravikumar Rramaswamy & , Ganesh Mani, Hyun Tae Jang (Journal of Applied Pharmaceutical Science, 2018)
A simple high molecular weight polyvidone (PVP) with tetrahydro curcumin (THC) loaded nanofiber was prepared and in-vitro dissolution was evaluated. Various polymeric concentration solution of PVP was prepared, from which 10% w/v PVP solution was used to load 10% w/w THC. The morphology of the prepared nanofibers was evaluated using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform-infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and ultraviolet-visible (UV-Vis) spectroscopy. The prepared mat released around 91% of the loaded THC within the first 5 minutes of the dissolution evaluation, which might be suitable for a buccal delivery system with a higher dissolution rate.
Keywords: Polyvinylpyrrolidone, Nanofibers, Tetrahydro curcumin, Electrospinning, In vitro evaluations.